Good practice report : assessment of science, technology, engineering and mathematics (STEM) students. - Rice, John (Australian Learning and Teaching Council (ALTC), 2011)
This report deals with the subject of assessment in undergraduate science, technology, engineering and mathematics (STEM) courses. Assessment has traditionally been predominantly in the form of high stakes end-of-topic examinations. Other types of assessment occur during the course of a topic, such as take home assignments, tutorial exercises or laboratory reports. This customary regime of assessment supports the accepted view of an undergraduate education in STEM, that its primary goal is to produce graduates with an expertise in one of the STEM disciplines. This report reviews some projects that have challenged the traditional approach to STEM assessment, including the biosciences projects: the BioAssess project (PP5-32), the Inquiry skills project (CG8-763) and the Online assessment feedback project (PP5-41). [Overview, Conclusion, ed]